Metastasis from follicular lymphoma to an ovarian mature teratoma: a case report of tumor-to-tumor metastasis - Yusuke Sato; Mitsutake Yano; Satoshi Eto; Kuniko Takano; Kaei Nasu (BMC, 2023)
Abstract Background Tumor-to-tumor metastasis (TTM) is a rare but well-established phenomenon where histologically distinct tumors metastasize within each other. Here we report the first "known" case of follicular lymphoma that metastasized and extended to a mature ovarian teratoma. Case presentation A 59-year-old Japanese postmenopausal woman visited our hospital for a detailed examination of an ovarian tumor. Clinical imaging suggested it to be either teratoma-associated ovarian cancer with multiple lymph node metastases, or tumor-to-tumor metastasis from malignant lymphoma to ovarian teratoma. A bilateral adnexectomy and retroperitoneal lymph node biopsy were performed. Lined with squamous epithelium, the cyst constituted a mature ovarian teratoma, and the solid part showed diffuse proliferation of abnormal lymphoid cells. Immunohistochemically, the abnormal lymphoid cells were negative for CD5, MUM1, and CyclinD1, and positive for CD10, CD20, CD21, BCL2, and BCL6. Genetic analysis using G-banding and fluorescence in situ hybridization identified a translocation of t(14;18) (q32;q21), and we diagnosed tumor-to-tumor metastasis from nodal follicular lymphoma to mature ovarian teratoma. Twelve months after surgery, the patient showed no progression without adjuvant therapy. Conclusions The present case suggests that molecular approaches are useful in the diagnosis of TTM in mature ovarian teratomas when morphologic and immunohistochemical findings alone are insufficient for diagnoses.